THE ANALYSIS OF FIGURATIVE LANGUAGE IN BRUNO MARS’ SELECTED SONG LYRICS - Suhendar, Suhendar; Hermawan, Muhammad Aldi; Budiarto, Budiarto (STIBA IEC JAKARTA, 2023)
Analytically, this research engages literally works in analysing the figurative languages used in Bruno Mars’ song lyrics “Grenade” while the urgency of this research is the need for a thorough understanding of figurative language in the song’s lyrics. For this reason, the objectives of this research is to find out kinds, the most dominant usage and general meanings of figurative language in Bruno Mars’ selected song’s lyrics. As for the design of this research, the researchers used a qualitative method with descriptive approach. The previous researches which had already been undertaken by the other researchers are namely the analysis of figurative language in the song lyrics of nine songs belonging to Maroon 5, namely Shiver, Goodnight good night, The way I was, Moves like Jagger, Can't stop, Sweetest goodbye, Until you're over me, Ragdoll, and Woman. Meanwhile the other researcher conducted research regarding ”An Analysis of Figurative Language in Online Short Story Posted on The Jakarta Post” aimed to find some kinds of figurative languages used. Different from the abovementioned researches, this research focuses on finding the kinds, the most dominant usage and general meanings of figurative languages in Bruno Mars’ selected song’s lyrics “Grenade”. Accordingly, after analysing the lyrics of the chosen Bruno Mars’ song “Grenade”, there are seven different kinds of figurative languages identified namely hyperbole, alliteration, irony, idioms, repetition, symbol, and metaphor. And then, the most figurative language used in such Bruno Mars’ selected song lyrics “Grenade” is hyperbole. As for general meanings described in such song’s lyrics they constitute romantic relationships that include despair, happiness, loneliness, and other emotions.